1970
DOI: 10.1080/00288233.1970.10421596
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic use of calcined christmas island iron/aluminium phosphates

Abstract: Glasshouse pot trials with ryegrass, subterranean clover, and radish as indicator plants showed that calcined Christmas Island iron/aluminium phosphates (Calciphos) when finely ground and mixed into the soil gave yields equal to those from the use of granulated superphosphate. Localising the powder in spots significantly reduced the yields only in early harvests. Plant response was greatest to material calcined between 500°c and 700°c, and yields were lower from material calcined below 500'c than from that cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

1970
1970
1988
1988

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 4 publications
2
4
0
Order By: Relevance
“…The 6 P sources evaluated can be ranked in the following decreasing order of agronomic effectiveness when ryegrass was used: superphosphate ~ NCPR ~ SPR > CRP > > Calciphos > > TPR. The difference found between NCPR and superphosphate is consistent with that reported in the literature for the:;e 2 P sources (Engelstad et al 1974;Chien & Hammond 1978b), as is the difference between SPR and superphosphate (Hammond 1978), CRP and superphosphate (Powell et al 1980;Mackay et al 1980;Rajan 1981b), Calciphos and superphosphate (Buchan et al 1970), and TPR and superphosphate (Hammond & Leon 1977).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The 6 P sources evaluated can be ranked in the following decreasing order of agronomic effectiveness when ryegrass was used: superphosphate ~ NCPR ~ SPR > CRP > > Calciphos > > TPR. The difference found between NCPR and superphosphate is consistent with that reported in the literature for the:;e 2 P sources (Engelstad et al 1974;Chien & Hammond 1978b), as is the difference between SPR and superphosphate (Hammond 1978), CRP and superphosphate (Powell et al 1980;Mackay et al 1980;Rajan 1981b), Calciphos and superphosphate (Buchan et al 1970), and TPR and superphosphate (Hammond & Leon 1977).…”
Section: Discussionsupporting
confidence: 80%
“…Although oflittle agronomic value in the raw state, calcination at 550·C increases the agronomic performance of this material. Calciphos has been evaluated extensively in both the glasshouse and the field in New Zealand (Doak et al 1965;Buchan et al 1970;Muller 1970).…”
Section: Introductionmentioning
confidence: 99%
“…They suggested that 10% bentonite may be necessary for breakdown to give satisfactory plant responses. Buchan et al (1970) confirmed in pot trials that only pellets with 10% bentonite disintegrated completely in the soil, and Muller (1970) reported that, in a field trial, pelletised Calciphos with 8% bentonite gave pasture yields of 61% of those obtained from superphosphate. However, at that time, the higher cost of producing bentonite pellets relative to the lower cost of phosphate rock was not considered economical.…”
Section: Introductionsupporting
confidence: 53%
“…Nauru Island rock phosphate was considerably less effective, Doak et al (1965) showed that C-grade Christmas Island rock phosphate, which contains crandallite and millisite as well as apatite and is unsuitable for the manufacture of superphosphate by conventional means, could be calcined at about 450"c with resultant degradation of the crystal lattices and enhanced solubility of the phosphate content. Although Muller (1970) and Buchan et at. (1970) found that this finely ground CCIP gave yields equal to or slightly less than superphosphate in field and pot experiments, Elliott (1967) concluded from results offield trials carried out by the New Zealand Department of Agriculture that CCIP was only half as effective as superphosphate when compared on an equal phosphate content basis.…”
Section: Introductionmentioning
confidence: 95%